American Autobiography after 9/11 - Brown, Megan (Professor of English) (Book collections on Project MUSE., 2017)
In the wake of the 2001 terrorist attacks in the United States, American memoirists have wrestled with a wide range of anxieties in their books. They cope with financial crises, encounter difference, or confront norms of identity. Megan Brown contends that such best sellers as Cheryl Strayed's Wild, Elizabeth Gilbert's Eat, Pray, Love and Tucker Max's I Hope They Serve Beer in Hell teach readers how to navigate a confusing, changing world. This lively and theoretically grounded book analyzes twenty-first-century memoirs from Three Cups of Tea to Fun Home, emphasizing the ways in which they reinforce and circulate ideologies, becoming guides or models for living. Brown expands her inquiry beyond books to the autobiographical narratives in reality television and political speeches. She offers a persuasive explanation for the memoir boom: the genre as a response to an era of uncertainty and struggle.